Steve Handoyoâ€™s Creativity in the Arrangement of Orchestral Campursari Music - Manik, Astri Marita; Sunarto, Sunarto; Triyanto, Triyanto (Universitas Negeri Semarang, 2018)
This thesis aims to analyze the creative process of an arranger named Steve Handoyo in Semarang. The researcher used interdisciplinary approach with qualitative method and interpretative case study. The supporting data were collected from observation, interview, and documentation. Triangulation were used to maintain the validity of the data. The analysis of the data was in the sequence of data reductin, presentation, and verification. The findings shows that Steve Handoyoâ€™s creativity are projected in three elements of Barretâ€™s theory of creation, which are; (1) Conceptual Elements (impuls, feelings, ideas). This element is realized from Handoyoâ€™s experience in campursari and orchestra. He also uses his feelings and imagination as the source of creativity.(2) Operational Elements(media, materials, technique). The used media are computer, midi, VSD plug in, violin, drum, cuk, and keyboard. The musical materials came form his experience learning Campursari and Orchestra, while the technicalities developed from the combination of musical instruments, including violing, drum, and keyboard with the sampling of â€œviona houseâ€. (3) Synthesis Elements (persepsi bentuk visual). From his experiences, Steve Handoyo imagines to apprehend the work he is going to make. Based on findings and discussion, Steve Handoyo does not include all the elements of orchestral instruments into his work, the authors hope for Steve Handoyo's later work with orchestral music can be adjusted to the rules of orchestration that includes all elements of the Orchestral instrument so it does not sound just an orchestra feel.